2017
DOI: 10.1371/journal.pone.0174533
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and optimal size of hospitals: Results of a systematic search

Abstract: BackgroundNational Health Systems managers have been subject in recent years to considerable pressure to increase concentration and allow mergers. This pressure has been justified by a belief that larger hospitals lead to lower average costs and better clinical outcomes through the exploitation of economies of scale. In this context, the opportunity to measure scale efficiency is crucial to address the question of optimal productive size and to manage a fair allocation of resources.Methods and findingsThis pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(113 citation statements)
references
References 112 publications
(185 reference statements)
5
105
0
3
Order By: Relevance
“…CC-BY-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity. (which was not certified by peer review) decade that led the regional health services to close a significant number of local small dimension hospitals that generally have higher costs [5]. This lack of beds is confirmed by a recent study of the OECD that reported that our country counts 2.6 hospital beds per 1000 inhabitants [6], ranking Italy at the 19 th place over 23 countries with Germany having more than 6 beds per 1000 inhabitants.…”
Section: Introductionsupporting
confidence: 52%
“…CC-BY-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity. (which was not certified by peer review) decade that led the regional health services to close a significant number of local small dimension hospitals that generally have higher costs [5]. This lack of beds is confirmed by a recent study of the OECD that reported that our country counts 2.6 hospital beds per 1000 inhabitants [6], ranking Italy at the 19 th place over 23 countries with Germany having more than 6 beds per 1000 inhabitants.…”
Section: Introductionsupporting
confidence: 52%
“…They have a small number of beds for admitted patients. The size of the hospitals has real impacts on the health outcomes according to the recent literature (Giancotti, Guglielmo, & Mauro, 2017;Kristensen, Olsen, Kilsmark, & Pedersen, 2008). Whether the profit-seeking behavior of small private hospitals also exists for inpatient care is the next logical question.…”
Section: Table 3 Results Of Ols Spatial Lag and Spatial Error Modelmentioning
confidence: 99%
“…Therefore, hospitals cannot increase the number of admitted patients beyond their capacity. According to the empirical literature, the size of the hospital has a real impact on the final health outcome (Giancotti et al, 2017). As the small hospitals specialized in ambulatory care, therefore hospitals compete with hospitals in their neighborhood to attract more patients to increase their profit levels.…”
Section: Discussionmentioning
confidence: 99%
“…Economies-of-scale effects in hospitals have been explored at length in the health economics literature [see, e.g., Giancotti et al (2017) for a recent survey]. However, although the majority of studies find evidence of the existence of economies of scale, their magnitude and moderating circumstances remain subjects of debate.…”
Section: The Importance Of Volumementioning
confidence: 99%